Criticism of the Pro-LGBT’s Misinterpretation of the Quranic Verses on the Illegality of LGBT - M. Kholid Muslih; Munar Moh Shobirin; Netty Yuwanda; Jajang Supriatna (Jurnal Ushuluddin, 2022)
This study discusses various pro-LGBT arguments based on QS. al-Hujurat[49]:13 and QS. al-A’raf [7]: 80-84 and QS. Hud [11]:77-82. Then, the location of their mistakes in interpreting the verse is explained by showing Muslim commentators’ views on the verses used as arguments. To find out the strength and measure the scientificity of these arguments. From this problem, this research will discuss the arguments of LGBT supporters, which are justified by the verses they quote. The method used in this research is the descriptive method and critical analysis. The results of this study can be concluded in several points; First, LGBT and homosexuals have the same conception. Second, the arguments of LGBT supporters seem compelling. Third, the arguments based on the verses of the Qur’an seem far-fetched because there is no strong argument to reject the interpretation of the mufassir. Finally, the partial understanding of LGBT supporters does not reach the essence or content of the verse